Restore and rebalance : yoga for deep relaxation - Lasater, Judith Hanson, ....- (Boulder : Shambhala, 2017)
"Restorative yoga teacher Judith Hanson Lasater offers a program of yoga poses to help rebalance your mind and body and counteract the effects of chronic stress. Restorative yoga, says Judith Hanson Lasater, is active relaxation. It makes use of props to create positions of ease and comfort that facilitate relaxation and health. In this companion volume to her seminal bookRelax and Renew, Judith Hanson Lasater, a well-known and respected yoga teacher, offers a fresh set of restorative practices--with accompanying photos--to help balance and reset the body when you feel weak, fatigued, or stressed from your daily activities. They are especially beneficial for the times before, during, and after major life events, or when you are recovering from illness or injury. Lasater points out that restorative yoga is a wonderfully adaptive practice that can be tailored to people of all ages, all levels of yoga experience, and in all states of health. Yoga practitioners and teachers will appreciate this new collection of practices and sequences that build on concepts from the first volume"--
Keywords: HEALTH & FITNESS ; Pain Management; HEALTH & FITNESS ; Yoga; Hatha yoga; SELF-HELP ; Stress Management; Stress management